Bioenergetic consequences of alopecia induced by Dermacentor albipictus (Acari: Ixodidae) on moose ... - Welch, D.A.; Hudson, R.J.; Samuel, W.M. (University of Alberta Library, 1990)
Fasting metabolic rates, respiration rates, respiratory minute volumes, and fasted weights were measured on three yearling moose (Alces alces (L.)) (Artiodactyla: Cervidae) infested with 50,000 winter ticks, Dermacentor albipictus (Packard) (Acari: Ixodidae), and on two uninfested controls. Infestations produced no detectable effects on fasting metabolic rates or weight changes. The influence of tick-induced alopecia on lower critical temperatures could not be assessed because of warm temperatures during the winter and spring trials. Destruction of winter hair accompanied a reduction in respiratory minute volumes and respiration rates of heat-stressed moose. ...